A funnel plot to assess energy yield and oil quality for pyrolysis-based processes. (October 2016) - DeSisto, William J.; Wheeler, M. Clayton
Abstract: The conversion of biomass to hydrocarbon transportation fuels presents unique challenges that generally focus on maintaining high mass and energy yields while removing oxygen from the biomass. Among the many processes proposed and demonstrated, processes that can achieve this efficiently and economically will have a clear advantage. Currently, there is no graphical method to analyze such conversion processes. In this work, we introduce a Funnel Plot to indicate both product quality, in terms of oxygen removal, and energy yield, the energy retained in the product oil from the original biomass. The Funnel Plot is applied to literature data for several processes and compared to an idealized chemical conversion of biomass revealing some of the current challenges associated with biofuel production. Graphical abstract: Highlights: A Funnel Plot is presented for assessment of mass and energy yields and oil-quality for biomass-to-liquid processes. Inefficiencies in oxygen removal during solid to liquid conversion for various processes are visualized on the plot. Processes compared include catalytic, formate-assisted, and hydro-pyrolysis, and hydrothermal liquefaction.